One-stage procedure for open tibial fractures: feasible without orthoplastic surgery? - Pari, Carlotta; Raggini, Filippo; Paderni, Stefania; Bettinelli, Giulia; Salini, Vincenzo; Vicenti, Giovanni; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2021)
Background:Open tibial fractures are mostly the result of high-energy traumas and often involve severe injuries with extensive bone and soft tissue loss, damage of muscles and neurovascular structures. Over recent years, the growth of Ortho-Plastic teams, as a well-coordinated bone, joint and soft tissue treatment, contributed to change the approach to these fractures and to achieve higher successful results in lower limb salvage. Unfortunately, many hospitals cannot benefit of a combined team in emergency, and the orthopedic surgeon is forced to manage personally these kinds of traumas. Methods: We retrospectively reviewed all the open tibial fractures treated at our Orthopaedic Department over the last 10 years, in order to assess the treatments performed (one-stage fixation with Intramedullary Nailing or Open Reduction Internal Fixation – ORIF, versus two/multiple-stage fixation with temporary External Fixation followed by nailing or ORIF) and the differences in the outcome between the different methods. Purpose: Based on our experience and review of the literature, the purpose of this paper is to define what cases can be managed by a single-stage orthopaedic approach, and when the orthopaedist should lay down his arms in favor of other specialties.